Tales from Fern Hollow - Patience, John (United Kingdom, Peter Haddock Publishing, 2008)
Fern Hollow is a make-believe village, inspiring children to follow our animal friends as together they explore the world of Lord Trundle, Mrs. Merryweather and friends as they live their daily lives
Keywords: English -Fiction